Evaluation of the Pollen Production Potential of Local Honeybee Races in Waghimra, Ethiopia - Desale, Ertiban; Girmay, Ayalew; Lemma, Meresa; Tsegaye, Agazhe; Ibrahim, Yesuf; Bezabh, Amsalu; Bareke, Tura; Alene, Mulugeta (International Journal on Food, Agriculture and Natural Resources, 2025)
Bee pollen is an essential protein source for honeybee (Apis mellifera) colonies and a valuable nutritionally rich product for human consumption. This study evaluated the pollen production potential of local honeybee races and examined the effects of pollen harvesting on colony resources across three agro-ecological zones (highland, midland, and lowland) in Waghimra, Ethiopia. Thirty healthy colonies were selected in each agro-ecological zone and divided into pollen-trapped and non-trapped (control) groups. Pollen was collected weekly during peak flowering periods, and colony performance parameters, including adult bee population, brood area, nectar stores, and pollen stores, were measured using standard estimation methods. The results showed that colonies in the highland produced significantly higher mean pollen yields (102.81 ± 11.17 g/month/hive) than those in the midland (72.80 ± 5.84 g/month/hive) and lowland (69.68 ± 7.21 g/month/hive) agro-ecologies (p < 0.05). Pollen yield was also significantly higher in the first study year compared to the second year (p < 0.05). Pollen harvesting significantly reduced stored pollen area but did not significantly affect adult bee population, brood development, or nectar stores. The findings indicate that moderate pollen harvesting during peak flowering periods can be practiced without compromising colony performance. Highland agro-ecological conditions provide favorable environments for sustainable pollen production and improved apiculture productivity in Waghimra, Ethiopia.